"Nobody Hears a Silent Cry for Help": Suicide Attempt Survivors' Experiences of Disclosing During and After a Crisis. Issue 4 (1st October 2020) - Maple, Myfanwy; Frey, Laura M.; McKay, Kathy; Coker, Sarah; Grey, Samara
Abstract : Suicide remains an important public health issue across the globe. Until recently the medically dominated field of suicide prevention has neglected first-hand accounts of suicidal thoughts and behaviors from those who have survived prior suicide attempts. This qualitative research provides insight into the experience of suicide attempt, highlighting difficulties with disclosure of suicidal thinking prior to, and after, suicide attempts. Semi-structured interviews were undertaken with 31 adult suicide attempt survivors. The focus of the interviews was to explore their experience of suicide attempt and recovery. This paper reports on the complexity involved in disclosing suicidal thoughts or behavior prior to, at the time, or post attempt; the role that help seeking has when someone is acutely suicidal; and the challenges people have in finding their voice at these critical junctures. These factors are both inter- and intra-personal, and are influenced by stigma and lack of understanding of the suicidal state.